Behaviour of composite slab-beam systems at elevated temperatures : experimental and numerical investigation - Nguyen, T.-T. (2014)
This paper presents the experimental observations and results of three one-quarter scale composite slab-beam systems, 3.15 m by 3.15 m in plan, and tested in fire conditions. The tests aimed to examine the effects of unprotected interior secondary beams and edge rotational restraint on the behaviour of floor assemblies. The test results show that continuity of reinforcement in the slab over the supporting beams, and the presence of interior beams, can reduce the slab deflection and enhance its load-bearing capacity. Interior beams can be left unprotected without leading to a structural failure. The interior beams play a major role in helping the slab to move from biaxial bending stage to membrane behaviour, enabling the slab to mobilize higher tensile membrane forces. Rotational restraint along the protected edge beams induces intense stress concentration above these beams, resulting in more severe concrete crushing at the four corners and wide cracks over the edge beams. In addition to the experimental study, a numerical model using ABAQUS has been developed to simulate the tests. The numerical predictions agree well with the experimental results, showing that the proposed model is reliable. A shortcoming of the study is that the fire resistance performance of the specimens cannot be compared with those in practical design because a real furnace fire and small-scale fire tests were used due to limits of the furnace. However, the experimental results do provide basic information on the membrane behaviour in fire and also allow analytical methods and numerical models to be validated.